In Silico Feasibility Study of Carbon Ion Radiotherapy With Simultaneous Integrated Boost for Head and Neck Adenoid Cystic Carcinoma - Mastella, Edoardo; Molinelli, Silvia; Magro, Giuseppe; Russo, Stefania; Bonora, Maria; Ronchi, Sara; Ingargiola, Rossana; Jensen, Alexandra D.; Ciocca, Mario; Vischioni, Barbara; Orlandi, Ester (Frontiers in Oncology, 2021)
Purpose: In carbon ion radiotherapy (CIRT), a simultaneous integrated boost (SIB) approach has not been fully exploited so far. The feasibility of a CIRT-SIB strategy for head and neck adenoid cystic carcinoma (ACC) patients was investigated in order to improve treatment planning dose distributions. Methods and Materials: CIRT plans of 10 ACC patients treated at the National Center for Oncological Hadrontherapy (CNAO, Pavia, Italy) with sequential boost (SEQ) irradiation and prescription doses of 41.0 Gy(RBE)/10 fractions to low risk (LR)-CTV plus 24.6 Gy(RBE)/6 fractions to the high risk (HR)-CTV were re-planned with two SIB dose levels to the LR-CTV: namely 48.0 Gy(RBE) and 54.4 Gy(RBE). While planning with SIB, the HR-CTV coverage had higher priority, with fixed organ-at-risk dose constraints among the SIB and SEQ plans. The homogeneity and conformity indexes were selected for CTV coverage comparison. The biological effective dose (BED) was calculated to compare the different fractionation schemes. Results: Comparable HR-CTV coverage was achieved with the treatment approaches, while superior conformality and homogeneity was obtained with the SIB technique in both CTVs. With the SEQ, SIB48.0 and SIB54.4 the LR-CTV median doses were 50.3%, 11.9% and 6.0% higher than the prescriptions. Significant reductions of the median and near-maximum BEDs were achieved with both SIB dose levels in the LR-CTV. Conclusions: The SIB approach resulted in highly conformal dose distributions with the reduction of the unintended dose to the LR-CTV. A prescription dose range for the LR-CTV will be clinically defined to offer tailored personalized treatments, according to the clinical and imaging characteristics of the patients.